2021
DOI: 10.2138/am-2021-7496
|View full text |Cite
|
Sign up to set email alerts
|

Magnesio-lucchesiite, CaMg3Al6(Si6O18)(BO3)3(OH)3O, a new species of the tourmaline supergroup

Abstract: Always consult and cite the final, published document. See http:/www.minsocam.org or GeoscienceWorld [ T (Si 5.87 Al 0.13) 6.00 O 18 ] (BO 3) V (OH) 3 W [O 0.61 (OH) 0.39 ] 1.00 (sample #2). Magnesio-lucchesiite is an oxy-species belonging to the calcic group of the tourmaline supergroup. It is related to lucchesiite by the homovalent substitution Y Fe ↔ Y Mg, and to feruvite by the homovalent and heterovalent substitutions Y Fe ↔ Y Mg and Z Al 3+ + W O 2-↔ Z Mg 2+ + W (OH) 1-. The new mineral was approved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Another possible mechanism for substituting Ca into X site in low Li-tourmalines is the MgCaOAl -1 □ -1 (OH) -1 substitution (Henry and Dutrow 1990). The simpler variation of this substitution, the CaONa -1 (OH) -1 substitution, results in the magnesio-lucchesiite end member (Scribner et al 2021) and can have an influence on Ca-rich and F-poor compositions in the studied samples. Another common Ca-substitution in tourmalines, the X Na + Y Al = X Ca + Y Li substitution, produces liddicoatite end member (Henry and Guidotti 1985) and is unlikely in these low-Li tourmalines.…”
Section: Mineral Composition and Crystal Chemistry Of Tourmalinitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible mechanism for substituting Ca into X site in low Li-tourmalines is the MgCaOAl -1 □ -1 (OH) -1 substitution (Henry and Dutrow 1990). The simpler variation of this substitution, the CaONa -1 (OH) -1 substitution, results in the magnesio-lucchesiite end member (Scribner et al 2021) and can have an influence on Ca-rich and F-poor compositions in the studied samples. Another common Ca-substitution in tourmalines, the X Na + Y Al = X Ca + Y Li substitution, produces liddicoatite end member (Henry and Guidotti 1985) and is unlikely in these low-Li tourmalines.…”
Section: Mineral Composition and Crystal Chemistry Of Tourmalinitesmentioning
confidence: 99%
“…Along with the common schorl-dravite composition, their fluor-and oxy-dominant counterparts -fluor-schorl, fluor-dravite, oxy-schorl and oxy-dravite -are also present. Moreover, portions of the tourmaline are enriched in Ca resulting in fluor-uvite and magnesio-lucchesiite, which is tourmaline derived from uvite with O 2dominant at the W site and the sum of trivalent cations at Z above 5.5 apfu (Scribner et al 2021). Moreover, the areas with Ti-rich compositions having Ti > 0.25 apfu likely correspond to a potential new mineral species, "magnesio-dutrowite", which would be the Mgdominant analog of dutrowite (Biagioni et al 2020).…”
Section: Mineral Composition and Crystal Chemistry Of Tourmalinitesmentioning
confidence: 99%
“…Such veins contain tourmaline extremely enriched in Al (∼7.7 apfu) with the spinel phase corresponding to Fe-bearing spinel, (Mg 0.7 Fe 2+ 0.3 ) Σ1.0 (Al 1.9 Fe 3+ 0.1 ) Σ2.0 O 4 , as determined by energy dispersive spectroscopy analyses. Scribner et al (2021) identified in San Rocco a second occurrence of a solid solution between magnesio-lucchesiite and uvite relatively depleted in Al (∼5.6 apfu), in veins along fractures within a basic hornfels derived by contact metamorphism of serpentinite.…”
Section: Calcic Tourmalines From the Thermal Aureole Of The Monte Cap...mentioning
confidence: 99%
“…Prism faces are striated parallel to the c axis. It has a grey streak and shows no fluorescence, has a Mohs hardness of ~7½ (estimated by analogy with magnesio-lucchesiite; Scribner et al , 2021) and is brittle with a conchoidal fracture. The calculated density, based on the empirical formula and unit-cell volume refined from single-crystal X-ray diffraction (XRD) data, is 3.115 g/cm 3 .…”
Section: Appearance Physical and Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation